Language and Decoding Skills in Greek-English Primary School Bilingual Children: Effects of Language Dominance, Contextual Factors and Cross-Language Relationships Between the Heritage and the Majority Language - Papastefanou, Theodora; Powell, Daisy; Marinis, Theodoros (Frontiers in Communication, 2019)
Bilingual children are a heterogeneous population, as the amount of input and use of their languages may differ due to various factors, for example, the status of each language (majority, minority), which language is used in the school, and whether children are acquiring literacy in one or both languages. Their language ability depends to a large extent on the use of each language and on whether they each language at the same rate. The aim of the study was to investigate how primary school bilingual children in the UK perform on several domains of language and reading skills and how these relate to language dominance. Moreover, it addressed how this performance is affected by a range of contextual factors and whether there are cross-language relationships in the children’s language and reading abilities. Forty Greek-English bilingual children in Year 1 and Year 3 were tested on vocabulary, phonological awareness, morphological awareness, morpho-syntax, and decoding in Greek and English. The results showed that as a group, the children were Greek dominant before the age of 4 but English dominant now and confirm that language dominance could change even before children enter school and affects language and literacy skills equally. A strong relationship between language use and performance was only in evidence in the minority language, which suggests that parental effort should be directed towards the minority language because schooling appears to level out differences in the majority language. There was no negative relationship between the use of the heritage language and children’s language and reading performance in the majority language. In contrast, significant positive cross-language associations were revealed among vocabulary, phonological awareness, inflectional morphology and decoding skills. The practical implications of this study are that parents and teachers should be informed for the positive effects of heritage language use in and outside the home for the maintenance of the heritage language and for the development of the children’s language and literacy skills.